Power Deposition Profile and Suprathermal Energy Spectra From Modulated ECRH - Hartfuss, H. J.; Erckmann, V.; Kechriniotis, A.; Maassberg, H.; Romé, M.; W7-AS-Team; the (HNPS Advances in Nuclear Physics, 2020)
N/A